The Role of the Transcription Factor EGR1 in Cancer - Wang, Bin; Guo, Hanfei; Yu, Hongquan; Chen, Yong; Xu, Haiyang; Zhao, Gang (Frontiers in Oncology, 2021)
Early growth response factor 1 (EGR1) is a transcription factor that is mainly involved in the processes of tissue injury, immune responses, and fibrosis. Recent studies have shown that EGR1 is closely related to the initiation and progression of cancer and may participate in tumor cell proliferation, invasion, and metastasis and in tumor angiogenesis. Nonetheless, the specific mechanism whereby EGR1 modulates these processes remains to be elucidated. This review article summarizes possible mechanisms of action of EGR1 in tumorigenesis and tumor progression and may serve as a reference for clinical efficacy predictions and for the discovery of new therapeutic targets.